FIRM VALUE: KEPUTUSAN PENDANAAN PADA PERUSAHAAN PERBANKAN - Supeni, Nely; Sari, Maheni Ika; Mufida, Ana (LP2M Institut Teknologi dan Bisnis Asia Malang, 2022)
The purpose of this study was to determine the direct and indirect effect of profitability and liquidity variables on firm value, through capital structure as an intervening variable. The sample used in this study is 11 banking companies that will conduct a right issue in 2021. This type of research explanatory research. The type of data used is secondary data taken from the RTI Business application. The data analysis used is path analysis. The results of the analysis show that: (1) Profitability has no significant effect on Financing Decisions, (2) Liquidity has a significant effect on Financing Decisions, (3) Profitability has no significant effect on Firm Value, (4) Liquidity has no significant effect on Firm Value, (5 ) Financing decisions have no significant effect on Firm Value, (6) Financing decisions are not able to mediate the effect of profitability on Firm Value, (7) Financing decisions are not able to mediate the effect of liquidity on Firm Value.